Knowledge and practice of condom use in an urban adult community sample of the Northern Province, South Africa - Karl Peltzer (AOSIS, 2000)
There is a paucity of data concerning condom use, especially regarding knowledge about the correct use of condoms in South Africa. Therefore, the aim of the study is to investigate knowledge and sexual practices with reference to correct use of condoms among an urban adult community in the Northern Province. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.